Representasi bendera One Piece sebagai simbol protes di media sosial indonesia: Analisis wacana kritis - Faiz, Moh (Maliki Interdisciplinary Journal, 2025)
This study examines the transformation of the straw-hatted Jolly Roger flag from the One Piece series into a symbol of political protest and civil resistance on Indonesian social media throughout 2025. Using the Critical Discourse Analysis (Fairclough) approach, Representation Theory (Hall), and the concept of Fandom Activism, this study reveals how netizens—especially generation Z and fan communities—re-signify these fictional symbols as creative metaphors for rejection of economic injustice, silencing criticism, and authoritarianism. Through multimodal strategies (memes, Gear 5 GIFs, AR filters, TikTok duets, viral threads, and hashtags such as #SeruanBendera and #OnePieceRevolution), this symbol has managed to spread massively across platforms, creating a wave of fandom activism on a national and transnational scale. State repression efforts in the form of raids, confiscation of flags, and "anti-Pancasila" narratives have actually produced a significant Streisand effect, strengthening the legitimacy of the symbol and attracting attention and condemnation from Human Rights Watch and Amnesty International. The phenomenon of the "Flag Call" 2025 confirms that global popular culture has extraordinary political power when rearticulated by the younger generation in the digital space, as well as new evidence that symbolic repression in the social media era tends to backfire on power.